Objective-C for iPhone developers : - Brannan, James A. (McGraw-Hill Education, 2010)
Create your own iPhone and Mac OS X applications with ease. Objective-C for iPhone Developers: A Beginner's Guide shows you how to use the Objective-C programming language, Apple's Foundation framework, the iPhone SDK, and the Xcode development environment. The first stop for aspiring iPhone developers, this hands-on guide teaches you how to create versatile, innovative, and marketable apps in no time. Real-world examples throughout the book correspond with downloadable Xcode projects and video tutorials so you can get started with your first app right away.